Progress in Arctic coastal geomorphological research in times of rapid climate warming - Owczarek, Zofia; Stachowska-Kamińska, Zofia; Kostrzewa, Oskar; Szczypińska, Małgorzata (Quaestiones Geographicae, 2024)
Recognising the degree of climate transformations in the Arctic becomes vital, especially in times of rapid global climate change. The 21st century has seen a renaissance in Arctic coastal research. Here, we aim to present this recent progress. Moving from the European Arctic through the Siberian part and ending with the Canadian Arctic Archipelago (CAA), we describe how the region’s coasts have transformed. This work is mostly focussed on progress in coastal geomorphology, geohazards, and reconstructions of the paleoarchives, although we also address the future research challenges of cold region coastal environments.